Workshop Pendidikan Kesetaraan Gender bagi Mahasiswa Program Studi Ilmu Komunikasi FISIP UNTIRTA: Suara Perempuan Suara Perubahan - Neka Fitriyah; Husnan Nurjuman; Burhanudin Mujtaba; Nina Yuliana (Universitas Sultan Ageng Tirtayasa, 2026)
The issue of gender inequality is a long-standing issue whose efforts continue to be made, but the resulting problems continue to grow. Gender inequality has a broad impact on attitudes of marginalization, subordination, stereotyping, double burdens, and gender-based violence. Students in the campus environment are also vulnerable to experiencing unequal attitudes and/or becoming perpetrators of gender inequality. Therefore, a gender equality education workshop is needed so that students can understand the basic concepts of gender and avoid harmful and dangerous behavior. This activity was carried out in four stages: pre-test, education, simulation, and post-test. The target of this activity was students of the Communication Science study program, FISIP Untirta. The results of this activity indicate that students need to be provided with gender equality education in a more comprehensive and continuous manner. On average, participants do not have adequate knowledge regarding the concept of gender, gender equality, and gender issues. After receiving gender equality education, participants' knowledge and understanding of gender increased, meaning that participants understand the basic concepts of gender, gender issues, and gender issues.